Effect of substrate temperature on quality of copper film catalyst substrate: A Molecular Dynamics Study - Rinaldo Marimpul (Universitas Pendidikan Indonesia, 2017)
Copper film growth using thermal evaporation methods was studied using molecular dynamics simulations. The AlSiMgCuFe modified embedded atom method potential was used to describe interaction of Cu-Cu, Si-Si and Cu-Si atoms. Our results showed that the variations of substrate temperature affected crystal structure composition and surface roughness of the produced copper film catalyst substrate. In this study, we observed intermixing phenomenon after deposition process. The increasing of substrate temperature affected the increasing of the total silicon atoms had diffusion into copper film.